Canadian Family Physician Preferences on Updating the Classification System for Health Conditions and Related Issues. - GARIES, STEPHANIE; PATHIRAJA, DEWDUNEE HIMASARA; MCBRIEN, KERRY A.; DICKINSON, JAMES A.; CRAMPTON, NOAH; EASTWOOD, CATHY A.; SOUTHERN, DANIELLE A.; VAN BOVEN, KEES; NAPEL, HUIB TEN; O'BEIRNE, MAEVE; SINGER, ALEXANDER; OLAGUNDOYE, OLAWUNMI; et al. (Healthcare Policy, 2025)
Physician billing claims are used to inform health system planning and for other secondary purposes. In most provinces/territories, diagnoses are coded using a system adopted in 1979, the International Classification of Diseases version 9 (ICD-9). This study aimed to understand the perspectives of family physicians on updating ICD-9. Canadian family physicians completed an online patient vignette coding exercise and electronic survey to capture preferences on two newer coding systems (ICD-11; International Classification for Primary Care version 3 [ICPC-3]), compared with the current ICD-9 system. The focus of this paper is the survey data, which were analyzed descriptively. One hundred and sixty-one family physicians from six provinces participated. Over half of them (58%) stated that ICD-9 should be replaced, and 86% of them felt confident learning a new coding system. After the coding exercise, most participants reported that they were very or somewhat satisfied with both newer systems (77% for ICD-11; 73% for ICPC-3). Family physicians in our study support replacing the outdated ICD-9 system to better reflect their workload and patient complexity. This paper provides recommendations for provinces/territories considering modernizing physician billing requirements.